DESICION SUPPORT SYSTEM OF LAND SUITABILITY FOR CORN SEED VARIETIES - Mulyana, Sri; Syahputra, Rizky Yurdan (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2025)
Decision making in selecting suitable agricultural land is a key factor for the success of corn cultivation. The selection of agricultural land is still largely based on the experience of farmers, which lacks a strong analytical foundation, this can lead to a decrease in production as the evidenced in 2023, the dry corn kernel production decline by 12,5% compared to the previous year. This research develops a Decision Support System (DSS) to analyze land suitability for corn varieties by using the Analytical Hierarchy Process (AHP) method to calculate the priority weights of each evaluation criterion, and the Profile Matching (PM) method to rank agricultural. The research uses data from 22 sub-districts in Blitar Regency as alternatives and 5 types of corn varieties as ideal profiles. The ranking results of this research indicate that the best agricultural land for varieties V1, V2, V3, and V4 is in Sanankulon Sub-district, while for variety V5, it is in Doko Sub-district. The validity test results showed a “Strong” coefficient, and the reliability test yielded a Cronbach's alpha of 0.8019, indicating a